Making Malaysian research available through publishing in open access e-journals and e-prints - Abrizah, Abdullah; Kaur, Kiran; Edzan, N.N.; Zainab, Awang Ngah (2006)
Individual authors are making their research available by posting their articles to personal or institutional Web pages and to disciplinary repositories. The recent trend is to publish or self-archive in open-access journals and “e-print” (i.e., preprints or postprints) repositories, both of which make the full text of scholarly articles freely available to everyone on the open Internet. Electronic journals and electronic archives which are OAI compliant would help to solve Malaysian research visibility problems. Malaysian authors are already contributing to these archives since there is none locally. The open archives serve the authors by facilitating their self-archiving, ensuring the long-term preservation of their documents and by providing word-wide easy access to their papers. Shedding light on open access reveals that scholars in diverse disciplines are both adopting open access practices and being rewarded for it as that articles deposited in these repositories have begun to receive citations and have also begun to achieve impact value